Tinjauan Judex Factie Salah Menilai Alat Bukti Surat Baru Dalam Perkara Pembunuhan Menurut Pasal 339 KUHP - Indra Kelana Putra; Bambang Santoso, S.H., M.Hum (Verstek, 2017)
This research  aims to determine the reason cassation prosecutor filed an appeal in compliance with the provisions of Article 253 Criminal Procedure Code on the grounds judex factie misjudge new documentary evidence and determine whether the judgment of the Supreme Court judges in deciding the public prosecutor's appeal in accordance with the provisions of Article 256 of the Criminal Procedure Code.       This research takes the case in 2013 in Luwu Utara District, the criminal act of murder committed by Muh. Roynal, where the killings followed, accompanied or preceded by a criminal act committed with the intent to prepare or facilitate its implementation or to detach themselves and other participants in the case of criminal caught in the act, is a criminal offense under Article 339 Penal Code.       Based on the results of research and discussion that is generated, the public prosecutor can prove the suitability of the reasons contained in Article 253 paragraph (1) Criminal Procedure Code, especially the letter a. The reasons for the appeal that has been described is described by the prosecutor in a murder case can be seen where the location of Judex factie had misjudged new documentary evidence, it can be seen where the location of Judex factie have erred and misapplied the law. It can be concluded also that the Supreme Court judgment in deciding cassation murder case under Section 339 Penal Code in accordance with Article 256 of the Criminal Procedure Code, with the consideration that the assessment tool by Judex factie new evidence must be disregarded.      Keywords: Cassation, Judex facti, a new documentary evidence Tool